(untitled) (NAU Journal of Technology and Vocational Education, 2024)
Nigerian tertiary institutions seem to have embraced electronic record-keeping procedures in order to make records available at the right time and at the right place butthe extent to which secretaries of polytechnics in Edo and Delta States have adopted electronic record processing practices is not empirically known. In order to execute this study, one research question was raisedand two hull hypotheses were tested at 0.05 level of significance. The study adopted the descriptive survey design. Populationof 188 secretaries in polytechnics in the two states were used for the study without sampling and the size was not too large. A validated questionnaire by experts was used for data collection.Cronbach alpha method was used to establish the reliability of the instrument which yielded coefficients of 0.75. Mean and standard deviation were used to answer the research question and determine the homogeneity of respondents’ means while t-test was used to test the hypotheses at 0.05 level of significance. The findings of the study revealed that electronic records processingpractices were adopted in managing records in polytechnics in Edo and Delta States to a high extent. The findings also revealed that secretaries do not differ significantly in their mean ratings on their extent of adoption ofelectronic records processing practices in managing records in their institutions as a result of gender and years of working experience. The study concluded that secretaries in polytechnics in Edo and Delta States need further retraining exercises to enable them acquire new digital skills that will facilitate the art of utilizing modern electronic records processing activities for effective and efficient management of records. It was recommended among others that polytechnics should ensure that adequate, functional and modern facilities are available for secretaries and administrative staffs to enable them perform electronic record processing practices effectively and efficiently.